The effectiveness of employing 3D interchange graphics in a diffuse learning environment on the science skills of health and life path students in the secondary stage - Alqahtani, Khaled Nasser (Journal of Curriculum and Teaching Methodology, 2023)
The research aims to determine the effect of employing 3D interchange graphics in a diffuse learning environment on the scientific skills of health and life path students in the secondary stage. The research sample consisted of (60 students) from high school students in the three governorates of Taima, Duba and Amlaj in the Tabuk region, who were divided into two groups, an experimental group (30 students) and a control group (30 students), with 10 students in each of the three governorates’ schools. The research followed the semi experimental approach as well as the descriptive approach. A unit in biology based on 3D interchange graphics was designed and implemented on the experimental group, while the same lesson was taught to the control group using the traditional method, and then the dimensions of science skills were measured using the science skills measurement card- researcher’s design – pre and post. The results revealed that there were statistically significant differences (α≤0.05) between the average scores of students of the experimental group who studied using 3D animation in a diffuse learning environment and the average scores of students of the control group who studied in the traditional way in the post application of each dimension of the skills note card. In addition, the three-dimensional animation in the diffuse learning environment had a significant impact (according to the ETA equation) on the scientific skills of students in the health and life track at the secondary stage. The research recommends, the need to pay attention to the educational programs that employ 3D graphics, and it also recommends paying attention to developing teachers’ skills in using and designing 3D graphics and developing curricula by including 3D graphics in them, especially for science and mathematics courses.